AN ASSESSMENT OF THE CURRENT STATUS OF SCHOOL-BASED INSTRUCTIONAL SUPERVISION IN WEST SHOA ZONE DANDI WOREDA SECONDARY SCHOOLS - Mamo, Tadesse Regassa (Universitas Negeri Semarang, 2019)
The purpose of this study was to assess the current status of school based instructional supervision practices in secondary school of Dandi Woreda. Three basic questions were formulated, which emphasized to assess current status of school based instructional supervision practices in secondary school, contributions of instructional supervision and problems and issues, current status of school based instructional supervision in secondary schools of Dandi Woreda. To conduct the study, descriptive survey design was employed. The sampling technique employed was simple random sampling for sample secondary school of teachers and availability sampling technique for school based supervisors, principals, vice principals and secondary school supervisors. To this end, 97 teachers 30 school -based supervisors 5 principals, 4 vice principals and 2 secondary school supervisors. Questionnaire was the main data gathering instrument for this study. Thus, 94 teachers and 30 school- based supervisors filled the questionnaires. An interview was also conducted to enrich the quantitative data. As a result, principals, vice principals and secondary school supervisors were interviewed. Quantitative data collected through questionnaire was analyzed by using percentage, frequency and chi-square test by using SPSS v.20.o. The data gathered through interview was discussed in line with questionnaire. The results of the study reveal that the school based instructional supervisory practice were ineffective. School based supervisors were involved in the difficult task of supervision without having prior trainings. School supervisors were also inefficient in promoting professional competence of teachers. Furthermore, the study revealed that: lack of trained supervisory personnel, lack of support like manuals, lack of training and experience sharing session and inadequate communication skill of supervisors hinder proper implementation of school based supervision. Finally, to minimize the problems of school-based supervision in secondary schools, it is recommended to give relevant in-service trainings for supervisors to upgrade their supervisory skills and avail necessary resources like supervision manuals, guidelines etc. Moreover, suggestions were forwarded to solve the factors that hinder proper implementation of supervisory practices.